Brendan Buckley's universe and everything in it - Frazier, Sundee Tucker, 1968- (Delacorte Press, 2007)
Brendan Buckley, a biracial ten-year-old, applies his scientific problem-solving ability and newfound interest in rocks and minerals to connect with his white grandfather, the president of Puyallup Rock Club, and to learn why he and Brendan's mother are estranged.